Pengaruh kompres hangat terhadap nyeri leher pada penderita hipertensi esensial di wilayah Puskesmas Depok I, Sleman Yogyakarta - Siti Fadlilah (Caring : Jurnal Keperawatan, 2019)
Hypertension is increased blood pressure in the artery. Signs and indication arise from this disease are a dizzy, headache, pain in the nape of the neck (neck pain), easily angered, and hard to breathe. This neck pain can offend essential hypertension in daily patient activities. One of the non-pharmacological actions to decrease or overcome the neck pain is by a warm compress. The warm compress is giving a sense of warm/heat in a certain area. This research is purposed to find out the influence of warm compress towards neck pain in essential hypertension patients. This research is carried out in Puskesmas Depok I area, Sleman, Yogyakarta. Type of this research is quasi-experiment with pre-test post-test with control group design. Several samples consist of 40 respondents and divided into two groups, which are 20 respondents of the intervention group and 20 respondents of the control group. Statistic test used in this research is Wilcoxon and Mann Whitney tests. Before applying pre-test, 12 respondents (60%) are having moderate pain, and after giving warm compress (post-test), 17 respondents (75%) are having minor pain. There is a significant scale of neck pain before and after the warm compress treatment (p-value = 0,003) as well as contrast scale of neck pain between intervention group and control group (p-value = 0,000). There is the influence of warm compress towards neck pain in essential hypertension patients in Puskesmas Depok I area, Sleman, Yogyakarta.